Growth and Yield Responses of Three Soybean (Glycine max L.) Varieties to Different Dolomite Dosages on Saturated Soil Culture - Asmara, Bima; Pujiwati, Hesti; Widodo, Widodo; Anggraini, Septiana; Anandyawati, Anandyawati (BPFP Universitas Bengkulu, 2023)
The need for soybean commodities is increasing in line with increasing changes in population and public awareness of the importance of food nutrition. One of the efforts to increase soybean production is to improve crop cultivation by selecting superior varieties. The purpose of this study was to obtain soybean varieties that had the best growth response and yields by adding dolomite to a saturated soil culture (SSC). This research was carried out from November 2020 to February 2021 in the experimental land of the Department of Agricultural Cultivation, Faculty of Agriculture, University of Bengkulu. The design used was a randomized completely block design (RCBD) factorial pattern consisting of two factors. The first factor was the dolomite dose which consisted of 4 levels, namely 0 x Al-dd, 0.5 x Al-dd, 1 x Al-dd, and 1.5 x Al-dd. The second factor was soybean varieties consisting of Gepak Kuning, Dering 1, and Derap 1 varieties. The results showed that Gepak Kuning produced the best growth response and yield by adding dolomite to SSC.